Centimeter-scale, single-crystalline, AB-stacked bilayer graphene on insulating substrates. (6th September 2019) - Guo, Hui; Wang, Xueyan; Lu, Hongliang; Bao, Lihong; Peng, Hao; Qian, Kai; Ma, Jiajun; Li, Geng; Huang, Li; Lin, Xiao; Zhang, Yu-Yang; Du, Shixuan; et al.
Abstract: Bilayer graphene (BLG) attracts great interest in both scientific research and potential applications. To achieve integrated applications of functional devices, synthesis of large-scale, single-crystalline BLG with a controlled stacking structure on insulating substrates is highly desired. However, so far, only polycrystalline BLG has been fabricated on insulating substrates, with single-crystalline domains limited to about half a millimeter. Here, we demonstrate successful fabrication of centimeter-scale, single-crystalline AB-stacked BLG on insulating substrates. First, we epitaxially grow single-crystalline BLG on Ru(0 0 0 1) and then transfer it to insulating substrates by an oxygen-intercalation-assisted electrochemical approach. The oxygen atoms intercalated between the BLG and Ru effectively decouple the BLG from Ru, enabling its successful transfer to a SiO2 substrate, which makes it readily available to Si-based technologies. Low-energy electron diffraction, scanning tunneling microscopy, and optical characterization demonstrate that the BLG on SiO2 is centimeter-scale, single-crystalline, and AB-stacking. The carrier mobility is measured at about 2000 cm 2 V −1 s −1 . This work provides a promising platform for future applications of large-scale, single-crystalline, high-quality BLG.